HUBUNGAN PERSEPSI SISWA DENGAN HASIL BELAJAR MELALUI PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) DI KELAS X MA MUHAMMADIYAH PEKANBARU TAHUN AJARAN 2016/2017 - Eti Saraswati; Arnentis '; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this study is to find out the correlation between the students’ perception and the learning outcomes of the tenth grade students of MA Muhammadiyah Pekanbaru using the application of cooperative model Think Pair Share (TPS) academic year 2016/2017. The research was carried out from November until December 2016. The sample of this research was all of the tenth grade students of MA Muhammadiyah academic year 2016/2017 which consisted of 28 students. The learning outcomes consisted of the result of cognitive test, attitude observation sheet, and product scoring sheet. A closed-questionnaire consisted of 5 indicators and developed into 30 questions; a test consisted of 20 questions; and attitude observation sheet measured the curiosity, the critical, the discipline, and the responsibility; and the product scoring sheet consisted of 3 indicators such as the plan, the concept, and the product. All of closed-questionnaire items were valid and reliable. The reliability of the test which was analyzed by using Cronbach alpha was 0.77, 0,83, 0,85, 0,88, and 0,85 for each indicator. The validity of the test was analyzed by SPSS program 17.00. The analysis of the data was by converting the result into the criteria of scoring. Specifically for affective and psychomotor outcomes, were calculated by using a formula. The correlation of students’ perception and learning outcomes using the application of cooperative model TPS was analyzed by using product moment correlation. The correlation between the students’ perception and learning outcomes the application of cooperative model Think Pair Share (TPS) was obtained as follows: r value for the cognitive learning outcome was 0,57 which was included as average; r value for affective learning outcome was 0,54 which was included as average; and r value for psychomotor learning outcome was 0,23 which was included as low.Key Words: Correaltion, Cooperative Model TPS, Learning Outcomes